1981
DOI: 10.1111/j.1365-2648.1981.tb03221.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mothers' concerns regarding the care‐taking tasks of newborns with congenital heart disease before and after assuming their care

Abstract: This exploratory study sought to identify, during the newborn's hospitalization, mother's concerns regarding the care-taking tasks of their infants with congenital heart disease and to determine, 1 month subsequent to discharge, whether the mother's concerns had changed. The sample consisted of ten mothers of infants aged up to 2 months at the time of the first interview which was conducted in hospital. A second interview was conducted in the home of the subjects 1 month subsequent to discharge. The content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Far less often than stress, researchers have investigated the prevalence of worry or concern (Brosig, Mussatto, et al, 2007;Docherty et al, 2002;Lan et al, 2007;Maxwell & Gane, 1962;Pinelli, 1981). In the studies reviewed, the prevalence of worry and concern was found to be quite high.…”
Section: Worry and Concernmentioning
confidence: 94%
See 4 more Smart Citations
“…Far less often than stress, researchers have investigated the prevalence of worry or concern (Brosig, Mussatto, et al, 2007;Docherty et al, 2002;Lan et al, 2007;Maxwell & Gane, 1962;Pinelli, 1981). In the studies reviewed, the prevalence of worry and concern was found to be quite high.…”
Section: Worry and Concernmentioning
confidence: 94%
“…Other commonly identified stressors were the daily care of the child, which included administering multiple medications, difficulties with feeding, and dealing with behaviors that are associated with a CHD diagnosis, such as being difficult to soothe as an infant (Darke & Goldberg, 1994;Goldberg et al, 1990;Majnemer et al, 2006;Miles et al, 1989;Pelchat et al, 1999;Pinelli, 1981;Svavarsdottir & McCubbin, 1996;Torowicz et al, 2010). Research indicated that the daily care of the child was a stressor that correlated with the severity of the diagnosis.…”
Section: Parenting During the Course Of The Child's Illnessmentioning
confidence: 97%
See 3 more Smart Citations